Characterisation of Sewage Sludge and Municipal Solid Waste for Use as Cementitious Materials - Al-Kuwari, Mohammed Bin Saif; Hassan, Khaled E. (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
Volumes of accumulated solid waste materials of sewage sludge (SS) and municipal solid waste (MSW) in Qatar continue to increase annually with a potentially negative impact on the environment. This paper presents an innovative technology for the production of green cement and advanced construction products from SS and MSW. Chemical composition analyses of the solid waste materials indicated the presence of main oxides available in Portland cement, but at lower contents. The three solid waste materials were incinerated and ground to produce consistent powder materials of similar sizes to Portland cement. The physical and chemical characteristics of the solid waste materials were investigated and compared to that of Portland cement. Paste and mortar mixtures were prepared by replacing 25, 50, and 75% of Portland cement with the different solid waste materials. Solid waste materials were found to influence the fresh properties of concrete, mainly water demand and setting time. Increasing the content of solid waste materials resulted in reduced compressive strength at all tested ages. SS gave the best performance within the solid waste materials investigated. Recommendations are made on the effective use of solid waste materials in various construction applications.